2022
DOI: 10.3389/fpsyg.2022.997984
|View full text |Cite
|
Sign up to set email alerts
|

Do I decide my career? Linking career stress, career exploration, and future work self to career planning or indecision

Abstract: Career planning and career decision are important tasks for college students. The process may be affected by career stress, career exploration, and future work self, with some students facing career indecision. Combining both construction career and proactive motivation model, this study investigated the relationships between career stress, career exploration, future work self, career planning and career indecision among 1,012 Chinese college students using the Structure equation model (SEM) to test the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…These results are aligned with the literature on career development at different points in the life cycle, when the importance of exploring all gained opportunities to plan and develop career paths is highlighted (Coimbra et al, 1994;Delors et al, 1996;Zhang et al, 2022), promoting a sense of preparedness to plan the involvement in new experiences (Savickas et al, 2009), thus, contributing to plan for the future (Zhang et al, 2022). Admitting that the development of each individual corresponds to the history of their development (Clot, 1999), the diversity of experiences also seems to be providing more opportunities to produce a reflection that allows self-knowledge and awareness of the alternatives, enhancing more productive and satisfactory career paths (Greenhaus et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results are aligned with the literature on career development at different points in the life cycle, when the importance of exploring all gained opportunities to plan and develop career paths is highlighted (Coimbra et al, 1994;Delors et al, 1996;Zhang et al, 2022), promoting a sense of preparedness to plan the involvement in new experiences (Savickas et al, 2009), thus, contributing to plan for the future (Zhang et al, 2022). Admitting that the development of each individual corresponds to the history of their development (Clot, 1999), the diversity of experiences also seems to be providing more opportunities to produce a reflection that allows self-knowledge and awareness of the alternatives, enhancing more productive and satisfactory career paths (Greenhaus et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…The importance of having previous career experiences is supported by recent findings with college students which identify that developing career exploration activities and actions positively influences their career planning preparedness (Zhang et al, 2022). When focusing on PhD students and their work experience, there seems to be a scarcity of studies focused on the career expectations of PhD students that consider their professional experience prior to enrolling in the Doctoral Program.…”
Section: The Career Development Of Phd Studentsmentioning
confidence: 99%
“…It is clear that the level of career stress will have significant effects on students' future work lives ( Zhang et al, 2022). For this reason, families, faculty members, university career centers, statesmen who carry out planning activities in higher education and students themselves have a lot of work to reduce career stress of students.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this framework, the future work self enables students to explore and rediscover themselves through the process of identity construction and to actively work toward a future that is consistent with their goals [ 48 ]. As it constitutes the positive possible selves and is a motivational resource in the context of work [ 11 ], studies have suggested that the future work self is positively linked to proactive career behaviors [ 16 , 49 ], such as career planning and skill development. Moreover, when shaping their future work self, students are more likely to seek relevant information and suggestions on environmental clues [ 15 ], which not only provides a clearer image of their occupational self-concept [ 50 ] but also forms “personalized” career planning for constructing themselves [ 51 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%